THE USE OF QRIS, SHARIA FINANCIAL LITERACY, SHARIA FINANCIAL INCLUSION AND PROMOTION TO INCREASE THE INCOME OF HALAL MSME ACTORS IN LHOKSEUMAWE CITY - Muhammad Hafizh; Mutia Rahmah; Noviami Trisniarti; Nabila Novianita; Safuani Marsya (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study aims to provide evidence of the relationship between the use of QRIS, Islamic financial literacy, Islamic financial inclusion and promotion on increasing the income of halal MSME actors in Lhokseumawe City. The population in this study is the community of halal MSME actors in the city of Lhokseumawe. The sampling technique used in this study is using the Slovin Formula method so that a sample of 96 Halal MSME actors is obtained. This research is a quantitative research using secondary data and primary data collected by questionnaire or questionnaire techniques. The questionnaire was analyzed using quantitative descriptive statistical analysis. with a significanty rate of 5%. Based on the results of the study, it was concluded that the research data was declared to be normally distributed, free from deviations from classical assumptions (multicollinearity, autocorrelation, heteroscedasticity). The test results stated that the independent variables (QRIS, Sharia Financial Literacy, Sharia Financial Inclusion and promotion) were able to explain the bound variable (Halal MSME Income) by 40.07%. Partially, the QRIS variable does not have a significant influence on the income of halal MSME actors, while Sharia Financial Literacy, Sharia Financial Inclusion and promotion have a partial effect on the income of Halal MSME actors. Which means that the higher the level of Sharia Financial Inclusion, the understanding of Sharia Finance in Halal MSME Actors, the more likely they are to get an increased income and become part of the main pillar of economic development policies which are very important to alleviate poverty, encourage sustainable economic growth.